Eucalyptus ESTs corresponding to the enzyme glutamine synthetase and the protein D1, sites of action of herbicides that cause oxidative stress - Velini, Edivaldo Domingues [UNESP]; Trindade, Maria Lúcia Bueno [UNESP]; Alves, Elza [UNESP]; Catâneo, Ana Catarina [UNESP]; Marino, Celso Luis [UNESP]; de Godoy Maia, Ivan [UNESP]; Mori, Edson Seizo [UNESP]; Furtado, Edson Luiz [UNESP]; Guerrini, Iraê Amaral [UNESP]; Wilcken, Carlos Frederico [UNESP] (FapUNIFESP (SciELO), 2005)
This work was aimed at locating Eucalyptus ESTs corresponding to the GS enzyme (Glutamine Synthetase, EC = 6.3.1.2) and to the D1 protein, which are directly related to resistance to herbicides that promote oxidative stress. Glutamine Synthetase corresponds to the site of action of the herbicide glufosinate. Herbicides that belong to groups such as ureas, uracils, triazines and triazinones act on the D1-Qb complex (receptor of electrons from the Photosystem II) by inactivating it. The clusters EGEQRT3302E01.g, EGEQRT3001F12.b; EGEZLV1203B04.g; EGBGFB1211H06.g and EGEZLV1205F09.g enclosed complete sequences (with 356 amino acids) of the Glutamine Synthetase enzyme. The cluster EGEQSL1054G06.g is a consensus of four reads and enclosed a complete sequence of D1 Protein (with 353 amino acids). The comparison of the sequences of Protein D1 from different species showed that the substitutions of serine (S) by glycine (G) or serine (S) by threonine (T) at the position 264 could produce plants resistant to herbicides that act on electron flow on Photosystem II. The sequence of amino acids corresponding to the cluster EGEQSL1054G06.g had a serine in position 264 indicating sensitivity of the Eucalyptus plants to herbicides that act on this site. Copyright by the Brazilian Society of Genetics.
Keywords: D1 protein; Eucalyptus; Glutamine synthetase; Herbicide; amino acid; glutamate ammonia ligase; glycine; herbicide; serine; threonine; triazine derivative; uracil derivative; urea; amino acid sequence; amino acid substitution; consensus sequence; controlled study; electron transport; enzyme active site; enzyme localization; expressed sequence tag; gene cluster; nonhuman; nucleotide sequence; oxidative stress; photosystem II; plant genetics; sensitivity analysis; species difference